The influence of institutional discourses on the work of informal carers: an institutional ethnography from the perspective of informal carers - Øydgard, Guro Wisth (BMC Health Serv Res, 2017)
BACKGROUND: The growing numbers of seniors worldwide and the need for support and services that follow from a higher standard of living have led to an increased focus on scarce benefits and limited human resources. At the same time, many western countries have had to make welfare cuts to balance budgets. This has brought the contributions of informal carers to the fore. Thus far, the focus has generally been on the need for the informal carers to receive information and support; to enable them to contribute. METHODS: The study is designed as an institutional ethnography. The article describes the social processes of informal caregiving and how it interacts with formal caregiving, from the perspective of informal carers. The research question for the study is How do institutional discourses on the work of informal carers influence informal carework? Data for the article comes from qualitative semi-structured interviews with 26 informal carers caring for persons with dementia in Norway, and with 7 administrators working in the allocation divisions of five different municipalities. RESULTS: The results demonstrate how three institutional discourses of informal carers’ work influence the allocation divisions’ practices and the work of informal carers in caring for their next of kin. The three discourses are categorised as moral and family obligation, shared care and task specificity. The informal carers want to contribute, as they feel a family and moral obligation to their next of kin. In the interaction with the allocation division, they find that the expectation that they will share in the carework and perform specific tasks forces them to perform care within a framework set by the public services. CONCLUSIONS: The findings suggest that further research should challenge how services are distributed and allocated rather than focus on how to enable informal carers to fulfil their role better. Because of their moral and family obligation, the informal carers do not have to be forced to perform certain tasks or parts of the shared care. To maintain the informal carers’ carework and to fully utilise their contributions, public services would benefit from collaborating with the informal carers to fulfil the total care need of the person with dementia.